Ansel's pharmaceutical dosage forms and drug delivery systems - Allen, Loyd V., Jr.; McPherson, Timothy B. (Philadelphia; New Delhi, India : Wolters Kluwer (India), 2005)
"The purpose of this text is to introduce pharmacy students to the principles, practices, and technologies applied in the preparation of pharmaceutical dosage forms and drug delivery systems. An integrated presentation is used in this textbook to demonstrate the interrelationships between pharmaceutical and biopharmaceutical principles, product design, formulation, manufacture, compounding, and the clinical application of the various dosage forms in patient care. Regulations and standards governing the manufacturing and compounding of pharmaceuticals are also presented"--
Introduction to drugs and pharmacy -- New drug development and approval process -- Current good manufacturing practices and current good compounding practices -- Dosage form design : pharmaceutical and formulation considerations -- Dosage form design : biopharmaceutical and pharmacokinetic considerations -- Powders and granules -- Capsules -- Tablets -- Solid oral modified-release dosage forms and drug delivery systems -- Ointments, creams, and gels -- Transdermals and transdermal drug delivery systems -- Suppositories, inserts, and sticks -- Solutions -- Disperse systems -- Parenterals -- Biologics -- Special solutions and suspensions -- Radiopharmaceuticals -- Products of biotechnology -- Novel dosage forms and drug delivery technologies -- Clinical pharmaceutics.
Copyright © 2018, 2014, 2011, 2005.
Includes bibliographical references and index.
PHR
Book Finder International
Keywords: Dosage Forms; Drug Delivery Systems; Pharmaceutical Preparations -- administration & dosage; Pharmacy